Penerapan Metode Weighted Product Dalam Pemantauan Kontaminasi Pada Ruang Kultur Jaringan Kelapa Sawit - Syafrial Nursaily; Aldianto Putra (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
Palm oil is a product that we usually use every day, even almost every day, companies in producing palm oil increase, so the demand for oil palm seeds increases, resulting in a lot of growing culture space to store oil palm tissue culture, as well as contaminants in the palm oil. The culture room is increasing so that the culture room must be cleaned using special treatment, so from monitoring the contamination in the culture room it must be increased so that the oil palm tissue culture is maintained in its growth, to avoid the decline in seedlings due to contamination, due to the culture room being not sterile, the problem faced by the company, namely the difficulty in determining the most highly contaminated culture room to be cleaned with special treatment. This is because the process of monitoring the culture room has not been computerized. Based on this, we need a method that can monitor to determine the highest contaminated culture room, namely the Weighted Product method. By applying the Weighted Product method, we are able to map something input into to produce output without ignoring the existing factors. The purpose of applying the Weighted Product method is to be able to monitor the oil palm tissue culture room and get the highest contaminated culture space value to make it easier to make decisions. The method used in this study is the Weighted Product method, while the prototyping method is used for system development. The research variables consist of factors that affect the dirtiness of the culture room such as bacteria, fungi, mites, humidity. Based on the results of the feasibility test that has been carried out, it can be obtained that the percentage of system expert eligibility is 93.7% and is interpreted as very feasible, while for the user eligibility percentage of 100%, the application made can be categorized into a proper interpretation.